2005
DOI: 10.1091/mbc.e04-09-0768
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mutant Phenotypes and Splicing Defects Demonstrates Functional Collaboration between the Large and Small Subunits of the Essential Splicing Factor U2AF In Vivo

Abstract: The heterodimeric splicing factor U2AF plays an important role in 3 splice site selection, but the division of labor between the two subunits in vivo remains unclear. In vitro assays led to the proposal that the human large subunit recognizes 3 splice sites with extensive polypyrimidine tracts independently of the small subunit. We report in vivo analysis demonstrating that all five domains of spU2AF LG are essential for viability; a partial deletion of the linker region, which forms the small subunit interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 62 publications
4
10
1
Order By: Relevance
“…For certain introns, such alternative interactions could provide the major contribution for early events during spliceosome assembly. A previous study on limited introns found no correlation between U2AF 59 requirement and the strength of the 5Ј splice site or other obvious features of pre-mRNAs; sequence features of the U2AF 59 -insensitive cdc16-I1 intron remained uncharacterized (58). Our study indicates the presence of a stronger 5Ј SS and a higher A/U percentage among the favorable features in U2AF 59 -insensitive introns ( Fig.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…For certain introns, such alternative interactions could provide the major contribution for early events during spliceosome assembly. A previous study on limited introns found no correlation between U2AF 59 requirement and the strength of the 5Ј splice site or other obvious features of pre-mRNAs; sequence features of the U2AF 59 -insensitive cdc16-I1 intron remained uncharacterized (58). Our study indicates the presence of a stronger 5Ј SS and a higher A/U percentage among the favorable features in U2AF 59 -insensitive introns ( Fig.…”
Section: Discussioncontrasting
confidence: 49%
“…For this discussion of the U2AF 59 requirement(s) for splicing, we have classified cellular introns as U2AF 59 sensitive, U2AF 59 insensitive, and conditionally sensitive, as suggested by previous studies of specific introns (54,58). Similar to the behavior of well-studied model introns, the U2AF 59 -sensitive cdc2_b intron showed the conventional U2AF 59 requirement (Fig.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In S. pombe, U2AF and BBP/SF1 form a stable complex (22). Unlike the mammalian introns, S. pombe introns show generally parallel requirements for both U2AF subunits (55). Moreover, various introns show FIG.…”
Section: Discussionmentioning
confidence: 99%
“…The heterozygous SpCR1 diploid (prp2::ura4/prp2 ϩ , ade6-M210/ade6-M216, ra4d18/ura4d18, leu1-32/leu1-32) and cdc2.2 and the Py tract variants (Y-long) (41), the prp2.1 mutant and the U2AF 59 genomic fragment plasmid pIRT3-prp2 ϩ (36), the U2AF 23 -ts mutant, (55), and the prp10-YH03 mutant (18) were previously described.…”
Section: Methodsmentioning
confidence: 99%